Microwave-assisted synthesis of carbon dots modified graphene for full carbon-based potassium ion capacitors - Dong, Shu; Song, Yali; Fang, Yongzheng; Zhu, Kai; Ye, Ke; Gao, Yinyi; Yan, Jun; Wang, Guiling; Cao, Dianxue (Carbon (New York), 2021)
Potassium ion batteries or capacitors are a promising technology for large-scale energy storage due to the abundant resource and low cost of potassium. However, the development of stable electrode materials with high capacity, capable rate ability, and excellent cycling stability remains a challenge. Herein, carbon dots modified reduced graphene oxides (LAP-rGO-CDs) are designed and synthesized via a rapid and green microwave-assisted method with l-Ascorbic acid 6-palmitate (LAP) as the reducing agent. LAP-rGO-CDs present enlarged interlayer spacing and faster ion transfer rate owing to the introducing of carbon dots. Serving as a potassium ion battery electrode, LAP-rGO-CDs showed a high specific capacity of 299 mAh g−1 at 1 A g−1 and excellent cycling stability. Moreover, a LAP-rGO-CDs//AC full carbon-based potassium ion capacitor is assembled and displays a maximum energy density of 119 Wh kg−1 and a power density of 5352 W kg−1. This work demonstrates the potential application of LAP-rGO-CDs for high-performance potassium ion storage. [Display omitted]